Análisis del ciberperiodismo en Ecuador: Contenido y evolución de medios - Gavilanez Quiroz, Evelyn Yascara (2021)
The case study that is presented mainly deals with the evolution of content in the media, cyberjournalism and freedom of expression, has as a line of Research of the Career of Social Communication, Sustainable Investigative Journalism Applied to New Technologies and as a Sub-line the Digital Communication. In the theoretical support, he makes a brief synthesis on traditional media, goes to the digital platforms YouTube, Instagram, Twitter, Facebook and how they have revolutionized contemporary society. The Methodology that is applied in this research project is qualitative-quantitative, it has the inductive-deductive method, it is a documentary type research, it uses the Survey as a technique and the questionnaire applied virtually to 25 students of the last year as an instrument. Social Communication Career- From the analysis carried out, it was found that a percentage of those surveyed did not know what cyberjournalism is. As a solution to the aforementioned situation, it is proposed to develop a Manual on digital journalism for students of Social Communication of the Technical University of Babahoyo for the adequate dissemination of information on social networks. Finally, the conclusions are presented after the analysis of the results of the survey taken to students in the last year of the Career of Social Communication, as well as the recommendations.